Análisis energético de una edificación mediante la herramienta de código abierto Openstudio - Chicaiza Rodríguez, Jonathan Andrés (2022)
In this research project, the analysis of energy efficiency in buildings is carried out using the open source tool OpenStudio applying regulations such as: ASHRAE 90.1-2016, Ecuadorian Construction Standard (NEC) and ARCONEL 003/18. In the first instance, a bibliographic research of energy efficiency regulations in buildings was carried out. Subsequently, information was sought about the architectural plans of the UTC Matriz building, monthly electricity consumption sheets for the year 2019 and a survey of electrical loads was carried out through an on-site visit. Then, three case studies were presented, consisting of simulating the building in OpenStudio software under current conditions, including HVAC systems such as heating, ventilation, hot water service that helps with thermal comfort and photovoltaic energy to reduce electricity costs. In addition, a comparison of photovoltaic energy production in MWh/year is made in both PVsyst and OpenStudio software.